OPTIMASI KAPASITAS PRODUKSI PADA UKM RUMAH KUE POYA - Miranda, Canda; Sirait, Ganda (Computer Science and Industrial Engineering, 2023)
This thesis discusses profit optimization in the cake production activities at Rumah Kue Poya located in Tiban, Batam City. The research aims to determine the optimal number of cake combinations that should be produced by Rumah Kue Poya to maximize profits. The data used in this study are secondary data obtained through documentation from Rumah Kue Poya. Subsequently, the research data is analyzed using linear programming with the simplex method using the POM-QM for Windows V.3 application, which is used to find the optimal solution. The results of this study indicate that to achieve optimal profits, Rumah Kue Poya should produce 5,500 pieces of risoles, 5,200 pieces of brownies, 2,500 pieces of cream puffs, and 2,500 pieces of donuts, with an optimal monthly profit of IDR 11,580,000 over a one-month period, representing a 1% increase in profit amounting to IDR 105,000 from the actual condition.